Expert System to Diagnose Soil and Plant Types According to The Web-Based Forward Chaining Method - Rizal Nur Ramadhan; Suprianto (Procedia of Engineering and Life Science, 2022)
Soil is a planting medium for farming which is used especially from the agricultural sector to produce various types of commodities from all types of plants. Meanwhile, there are several problems that occur in the middle of agriculture, one of which is the problem of soil acidity which results in a decline in crop yields which before the acidity of the soil did not have so many obstacles in farming. The purpose of this research is to produce an expert system application to diagnose suitable soil and plant types. The research method used is forward chaining, a method that seeks conclusions based on facts that are useful for farmers to be able to find out the ability of the type of soil they experience, so that farmers can handle the appropriate type of soil and plants. The results of this study use an expert system application that has been tested by several farmers to produce a diagnosis of the ability of the soil type so that it can determine the type of soil and plants that are suitable and also as a medium of consultation for farmers. So it can be concluded that the Forward Chaining Expert System is quite feasible to be used by users, in this case farmers, in diagnosing the ability of soil types.